Modelling the time course of antimalarial parasite killing: A tour of animal and human models, translation and challenges - Patel, K.; Simpson, J.; Batty, Kevin; Zaloumis, S.; Kirkpatrick, C. (Blackwell Publishing, 2015)
Malaria remains a global public health concern, and current treatment options are sub-optimal in some clinical settings. For effective chemotherapy, antimalarial drug concentrations must be sufficient to completely remove all of the parasites in the infected host. Optimised dosing therefore requires a detailed understanding of the time course of antimalarial response, whilst simultaneously considering the parasite life-cycle and host immune elimination. Recently, the World Health Organisation (WHO) has recommended the development of mathematical models for better understanding antimalarial drug resistance and management. Other international groups have also suggested that mechanistic pharmacokinetic (PK) and pharmacodynamic (PD) models can support the rationalisation of antimalarial dosing strategies. At present, artemisinin-based combination therapy (ACT) is recommended as first line treatment of falciparum malaria for all patient groups. This review summarises the PK-PD characterisation of artemisinin derivatives and other partner drugs from both preclinical studies and human clinical trials. We outline the continuous- and discrete-time models that have been proposed to describe antimalarial activity on specific stages of the parasite life-cycle. The translation of PK-PD predictions from animals to humans is considered, because preclinical studies can provide rich data for detailed mechanism-based modelling. While similar sampling techniques are limited in clinical studies, PK-PD models can be used to optimise the design of experiments to improve estimation of the parameters of interest. Ultimately, we propose that fully developed mechanistic models can simulate and rationalise ACT or other treatment strategies in antimalarial chemotherapy.